MICROVESICLES AND THROMBOSIS IN OBSTETRIC-GYNECOLOGICAL COMPLICATIONS - A. Aharon; B. Brenner (IRBIS LLC, 2016)
Microvesicles (MVs), including microparticles and exosomes, are secreted from a variety of cells. They are present in the blood circulation under normal physiological conditions, and their levels increase in a wide range of disease states. MVs contain proteins, growth and apoptotic factors, DNA fragments, microRNAs as well as messenger RNAs (mRNAs); therefore, they may function as regulators in cell-cell communication and mediators of cell signaling during multiple biological processes. The current review focuses on the role of MVs in healthy pregnancy and gestational vascular complications and discusses the involvement of MVs in thrombosis, hemostasis and cell function that overall reflect the placental-maternal crosstalk.